Advection-Diffusion Equation for Prediction of Air Pollution Parameters - Dione, Déthié; Koné, Bakary; Dosso, Mouhamadou; Espérance, Tapé Grace (Journal of Applied Nonlinear Dynamics, 2026)
The dispersion of pollutants in the atmosphere takes place mainly in the atmospheric boundary layer, the most turbulent layer, which is constantly agitated by turbulent movements. This dispersion is influenced by several parameters, such as wind speed and diffusivity, among others. In this paper, we are interested in studying these parameters influencing air pollution, using advection-diffusion equations. This study will first comprise discretizing our different equations by an implicit finite difference method. Then we solve these discretized advection-diffusion equations using an adapted MATLAB program. The results obtained allow us to predict the air quality, which is deduced from the concentration rate of the pollutants in time and space.